Perancangan dan Penerapan Kanban di PT. X - Claudio Giano Tombeg (Jurnal Titra, 2017)
PT. X is a circuit breaker manufacturing company. The main problem at segment XYZ is production delayed, that is caused by less availability of BG Bimetall product. Line efficiency of BG Bimetall production line is 74,33% and ABC process have the longest production time. The design of kanban is needed to fulfill material requirement in BG Bimetall, so supply material in this process should not be delayed. The kanban design consist of kanban size calculation (1 kanban), kanban box design, and kanban card design for kanban signal. After implementation, BG Bimetall production line still has longer lead time (1077,59 minutes) than assembly production line (491,845 minutes). Several improvement suggestions to reduce BG Bimetall lead time are reducing setup time, eliminating unnecessary movements, and implementing overtime hour at BG Bimetall.